TEKNOLOGI PROGRAM ANALISIS PENERAPAN GERTAK TANPA DUSTA USAHATANI PADI SAWAH DI KABUPATEN TANJUNG JABUNG TIMUR - Suandi; edison; Ahmadi, Peki (JALOW | Journal of Agribusiness and Local Wisdom, 2021)
In an effort to increase national rice, it is known that rice reserves in Indonesia have experienced a shortage. Farmers are required to participate in building national food strength through increased productivity. The Bullying Without Lies Program is one of the efforts of the East Tanjung Jabung District Government to achieve the target of achieving sustainable self-sufficiency through increasing productivity/production. The success of a program is irnfluernced by interrnal and external factors of farmers in the field. The research that will be conducted is expected to provide feedback information on farmers' understanding of the application of technological for the Bullying Without Lies Program Farming for Rice Field Farming as an effort to increase rice productivity/production. This research takes place in East Tanjung Jabung Regerncy and the object of research is all members of farmer groups who carry out or participate in the Bullying Without Lies Program in East Tanjung Jabung District. The sampling technique used was by random sampling, so that the respondents in this study where 87 farmers. The results of the study using descriptive analysis and SEM (Structural Equation Model) using the PLS program showed that the interrnal and external factors of farmers and characteristics of innovation on the application of technology to the Bullying Without Lies Program were in the good category with the value of QÂ² (95.52%). The results of the path analysis show that the internal factors of farmers and external factors of farmers have a significant and significant effect on the variable of technology application of the Bullying Without Lies Program through the moderating variable of innovation characteristics of 0.772